Developing a curriculum blueprint and taxonomy: Process, progress, and pivots. Issue 12 (20th September 2020) - Wolcott, Michael D.; Quinonez, Rocio B.; Tittemore, Ashley J.; LaGarry‐Cahoon, Alison; Zomorodi, Meg; Reside, Jonathan M.; Jackson, Tate H.
Abstract: Curriculum transformations represent opportunities to innovate; however, there are few examples to inform this process. In 2018, the University of North Carolina at Chapel Hill (UNC) Adams School of Dentistry began to transform the predoctoral curriculum to improve content integration, enhance team‐based experiences, and develop leaders. Part of this experience has been crafting a conceptual curriculum guide or "blueprint" that outlines a vision for the design process and ensures the transformation achieves its goals. We describe how we created the UNC Blueprint for our revised curriculum, which defines who our graduates are, what they know, and what they can do . This approach has led us to develop a mapping taxonomy to ensure the student outcomes are appropriately aligned with content, instruction, and assessment throughout the curriculum. Last, we encourage others to be agile in their approach, create a common language among their teams, and frequently engage faculty to facilitate the process.